Autophagy induction regulates aquaporin 3‐mediated skin fibroblast ageing. (1st February 2022) - Xie, H.; Zhou, L.; Liu, F.; Long, J.; Yan, S.; Xie, Y.; Hu, X.; Li, J.
Summary: Background: Long‐ and short‐term ultraviolet (UV) exposure have distinct biological effects on human fibroblasts. Objectives: To elucidate the underlying mechanisms of the biological effects of UV exposure on human skin fibroblasts. Methods: We subjected human skin fibroblast cells with or without aquaporin 3 (AQP3), death effector domain‐containing protein (DEDD) or Beclin1 manipulation to UVA treatment and evaluated autophagy and senescence in them. Results: Short‐term UVA irradiation induced autophagy and upregulated AQP3 but not senescence, whereas long‐term UVA irradiation inhibited autophagy, AQP3 and trigger senescence in vitro and in vivo . Silencing AQP3 abolished short‐term UVA irradiation‐induced autophagy and led to cellular senescence, whereas AQP3 overexpression partially rescued the senescence and autophagy inhibition induced by long‐term UVA exposure in vitro . Mechanistically, the transcription factor Jun was found to bind to the AQP3 promoter to activate its transcription following short‐term UVA exposure. Subsequently, AQP3 interacted with DEDD to induce its ubiquitination‐mediated degradation and promote autophagy, and bound to Beclin1 to directly activate autophagy. Finally, autophagy induced by AQP3 overexpression robustly prevented UVA‐induced senescence in vitro and in vivo . Conclusions: Our study indicates that AQP3 controls skin fibroblast photoageing by regulating autophagy and represents a potential target for future interventions against skin ageing.